2009
DOI: 10.1109/tpami.2008.136
|View full text |Cite
|
Sign up to set email alerts
|

Combining Slanted-Frame Classifiers for Improved HMM-Based Arabic Handwriting Recognition

Abstract: The problem addressed in this study is the offline recognition of handwritten Arabic city names. The names are assumed to belong to a fixed lexicon of about 1,000 entries. A state-of-the-art classical right-left hidden Markov model (HMM)-based recognizer (reference system) using the sliding window approach is developed. The feature set includes both baseline-independent and baseline-dependent features. The analysis of the errors made by the recognizer shows that the inclination, overlap, and shifted positions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(17 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…In addition, IFN/ENIT information was utilized for testing and training, and maximum recognition rates of 89% were observed. For the detection of offline Arabic handwriting, Al-Hajj et al [ 10 ] suggested an arrangement of three right-to-left HMM classifiers. All classifiers were built upon specific sliding window orientations in order to surmount the significant difficulties of offline handwritten words, including overlaps, inclinations and the shifted positions of diacritics.…”
Section: Previous Workmentioning
confidence: 99%
“…In addition, IFN/ENIT information was utilized for testing and training, and maximum recognition rates of 89% were observed. For the detection of offline Arabic handwriting, Al-Hajj et al [ 10 ] suggested an arrangement of three right-to-left HMM classifiers. All classifiers were built upon specific sliding window orientations in order to surmount the significant difficulties of offline handwritten words, including overlaps, inclinations and the shifted positions of diacritics.…”
Section: Previous Workmentioning
confidence: 99%
“…Total number of parameters depends on w window size. Each frame consists of a set of features which have been successfully applied to HMM-based latin and arabic handwritten word recognition [9], [10] and recently to text lines recognition [19]. These features are the following: In order to extract features, each window is divided into a fixed number of cells.…”
Section: B Blstm Modelmentioning
confidence: 99%
“…Thus we only test a few state number values. Following previous work [10], we restricted the step parameter to the range [2,4] and the window width to [8,9].…”
Section: B Feature Extraction Optimizationmentioning
confidence: 99%
See 1 more Smart Citation
“…El-Hajj in [11] presented a system for the off-line recognition of handwritten Arabic city names. The system was based on the HMM applied with a set of features including both the independent baseline and the dependent one.…”
Section: Review Of Offline Handwritten Word Recognition Approachesmentioning
confidence: 99%